Perubahan Motivasi Siswa Mata Pelajaran PAI dengan Model Pembelajaran Examples Non Examples - Lilis Hidayati; Yuyun Zunairoh (MANAGIERE: Journal of Islamic Educational Management, 2023)
This research aims to help teachers increase students' learning motivation by using the Examples non Examples learning model in PAI subjects in class VII D of SMP Negeri 1 Bareng Jombang. This research was motivated by low student learning motivation which also resulted in low student learning activity. After conducting Classroom Action research, there was an increase in student learning motivation from cycle I to cycle II. In cycle I, student learning motivation was 65.5%, while in cycle II it increased to 92.8%. Through the application of the Examples non Examples learning model, student learning motivation can be increased so that the learning process is carried out well. The teacher's role in implementing appropriate learning models during the learning process is very important because it can improve the quality of student learning both in terms of motivation and learning outcomes.